Antenatal antiarrhythmic treatment for fetal tachyarrhythmias: a study protocol for a prospective multicentre trial. Issue 8 (29th August 2017) - Miyoshi, Takekazu; Maeno, Yasuki; Sago, Haruhiko; Inamura, Noboru; Yasukochi, Satoshi; Kawataki, Motoyoshi; Horigome, Hitoshi; Yoda, Hitoshi; Taketazu, Mio; Shozu, Makio; Nii, Masaki; Hagiwara, Akiko; et al.
Abstract : Introduction: Several retrospective or single-centre studies demonstrated the efficacy of transplacental treatment of fetal tachyarrhythmias. Our retrospective nationwide survey showed that the fetal therapy will be successful at an overall rate of 90%. For fetuses with hydrops, the treatment success rate will be 80%. However, standard protocol has not been established. The objective of this study is to evaluate the efficacy and safety of the protocol-defined transplacental treatment of fetal tachyarrhythmias. Participant recruitment began in October 2010. Methods and analysis: The current study is a multicentre, single-arm interventional study. A total of 50 fetuses will be enrolled from 15 Japanese institutions. The protocol-defined transplacental treatment is performed for singletons with sustained fetal tachyarrhythmia ≥180 bpm, with a diagnosis of supraventricular tachycardia or atrial flutter. Digoxin, sotalol, flecainide or a combination is used for transplacental treatment. The primary endpoint is disappearance of fetal tachyarrhythmias. The secondary endpoints are fetal death related to tachyarrhythmia, proportion of preterm birth, rate of caesarean section attributable to fetal arrhythmia, improvement in fetal hydrops, neonatal arrhythmia, neonatal central nervous system disorders and neonatal survival. Maternal, fetal and neonatal adverse events are evaluated at 1 month after birth. Growth and development are also evaluated at 18 and 36 months of corrected age. Ethics and dissemination: The Institutional Review Board of the National Cerebral and Cardiovascular Center of Japan has approved this study. Our findings will be widely disseminated through conference presentations and peer-reviewed publications. Trial registration number: UMIN Clinical Trials Registry UMIN000004270.